Hijrah Movement: Search for Identity Young Islamic Religious Education Students in the Millennial Era - Amirudin, Noor (Universitas Muhammadiyah Ponorogo, 2024)
This article aims to explore the search for identity of Islamic religious education students in the millennial era that is happening in the current era. The millennial Muslim student movement has built a new identity as a religious community that adheres to Islamic principles. Hijrah as their lifestyle aims to get closer to straight faith and spread the message of Islam. To hone this background, a qualitative approach is needed, with the type of research being a case study. That in the activities of Islamic Religious Education students at Muhammadiyah University of Gresik, they are careful in their attitudes and actions when interacting with fellow Muslims and non-Muslims in order to live in harmony and tolerance. Not only that, they also emphasized that lecturers should become figures in their lives to get to know the basics of Islam which can strengthen their Islamic commitment. Furthermore, their identity as young students in general, with their participation in the hijrah movement there is a construction of their identity and cultural framing as young students who are social but adhere to the Islamic religion.